Strategies for the Management of Risks in Sports for Sports Administrators in State Sports Councils, South East, Nigeria - Chukwurah, Linda N.; Nji, Godfrey C.; Nwokoji, Michael; Umeakuka, O.A. (European Scientific Journal, ESJ, 2017)
Risks cannot be completely eliminated from sports hence the need to formulate strategies for the management of risks in sports such as risk of injury, risk of financial or monetary loss and risk of damaging of sports facilities. The study involved seven experts. A 33 items Risk Management Strategies for Sports Administrators Questionnaire (RMSSADsQ) was used for data collection. Copies of the questionnaire were given to the experts to rate the appropriateness of the proposed strategies and the data were analyzed using Statistical Package for Social Sciences (SPSS) version 21. 2.50 was used as the criterion mean which implies that any item with less than 2.50 mean score was not considered as a strategy. 30 out of the 33 items were adjudged appropriate as strategies for managing risks in sports. Based on the findings, the researchers therefore recommend that sports administrators should adopt or adapt the formulated risk management strategies in order to enhance effective handling of risks in sports in their various sports councils and organizations.